Estimation Liquid Permeability Using Air Permeability Laboratory Data - Abdulwahid Al-Sudani, Jalal; Kaiser; Salam, Rwaida; J. Al-Rubeai, Salam (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Permeability data has major importance work that should be handled in all reservoir simulation studies. The importance of permeability data increases in mature oil and gas fields due to its sensitivity for the requirements of some specific improved recoveries. However, the industry has a huge source of data of air permeability measurements against little number of liquid permeability values. This is due to the relatively high cost of special core analysis. The current study suggests a correlation to convert air permeability data that are conventionally measured during laboratory core analysis into liquid permeability. This correlation introduces a feasible estimation in cases of data loose and poorly consolidated formations, or in case of the unavailability of old cores to carry out liquid permeability. Moreover, the conversion formula offers a better use of the large amount of old air permeability data obtained through routine core analysis for the further uses in reservoir and geological modeling studies. The comparison analysis shows high accuracy and more consistent results over a wide range of permeability values for the suggested conversion formula.